On Generalized Primitive Recursive String Functions - Khachatryan, Mikayel H. (Mathematical Problems of Computer Science, 2021)
The notion of generalized primitive recursive string function is introduced and relations between such functions and primitive recursive string functions in the usual sense ([1], [2]) are investigated. It is proved that any generalized primitive recursive string function is everywhere defined if and only if it is a primitive recursive string function in the usual sense.